The crisis of the metaphysical foundations of human existence as a global problem of post-modernityand the ways of managerial solutions - Nikitenko, Vitalina A (2021)
The relevance of the study of the crisis of the metaphysical foundations of human existence is due to the fact that humanity is in a crisis of global development of the world associated with the Fourth Industrial Revolution 4.0, the technological development of the world, the demographic and environmental crisis, the epidemic of the coronavirus COVID-19. The purpose of the study is to conceptualize the socio-philosophical reflection of the crisis of the metaphysical foundations of human existence, which is a global problem of our time, which threatens our civilization, is associated with economic and social development, with many problems, including the problem of COVID-19. The objectives of the research are to identify the problems of the metaphysical dimensions of human existence and find ways that promise to lead to great achievements - to raise living standards, create new economic opportunities, solve anthropological, existential and ontological problems of human being associated with the real de-objectification of human existence, loss of the integrity of self-determination.The scientific novelty of the research is that it presents a solution to new problems of the crisis of the metaphysical foundations of human existence and ways to solve them.